Language development, delay and intervention—the views of parents from communities that speech and language therapy managers in England consider to be under‐served. Issue 4 (20th December 2016) - Marshall, Julie; Harding, Sam; Roulstone, Sue
Abstract: Background: Evidence‐based practice includes research evidence, clinical expertise and stakeholder perspectives. Stakeholder perspectives are important and include parental ethno‐theories, which embrace views about many aspects of speech, language and communication, language development, and interventions. The Developmental Niche Framework provides a useful theory to understand parental beliefs. Ethnotheories, including those about language development, delay and interventions, may vary cross culturally and are less well understood in relation to families who may be considered 'under‐served' or 'hard‐to‐reach' by speech and language therapy services. Who is considered to be under‐served and the reasons why some families are under‐served are complex. Aim: To describe beliefs and reported practices, in relation to speech and language development, delay and intervention, of parents and carers from a small number of groups in England who were perceived to be under‐served in relation to SLT services. Methods & Procedures: As part of a wider National Institute for Health Research (NIHR)‐funded study (Child Talk), seven focus groups (with a total of 52 participants) were held with parents from three communities in England. Topics addressed included beliefs about language development, language delay and parents' reported responses to language delay. Data were transcribed and analysed using adapted framework analysis, which also drew on directed content analysis. Outcomes & Results: Four themes resulted that broadly matched the topics addressed in the focus groups: language development and the environment; causes and signs of speech and language delay; responses to concerns about speech, language and communication; and improving SLT. These produced some previously unreported ideas, e.g., about how language develops and the causes of delay. Conclusions & Implications: The findings are discussed in relation to previous literature and the Developmental Niche Framework. Clinical implications include ideas about issues for SLTs to discuss with families and the need to recognize that parents may see themselves as competent facilitators of language. Suggestions are made for future research, including: expanded investigation of a wider range of under‐served groups, an exploration of who parents consult when concerned about their child's language, and how key community figures advise parents in relation to language delay.